2017
DOI: 10.21037/jtd.2017.11.90
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of supplementary diagnostic value of contrast-enhanced ultrasound for lymph node puncture biopsy

Abstract: Background: Contrast enhanced ultrasound (CEUS) is an effective way to evaluate the distribution of micro vessels in organs with little invasiveness. The qualitative evaluation and differential diagnosis of lymph node is essential for a number of clinical situations, including appropriate examination selection, oncologic staging, therapy and prognosis beyond diagnosis itself. The purpose of this study is to investigate the contribution of characterization of cervical lymphadenopathies on CEUS as an indication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A global hypoechoic (i.e. pseudocystic) appearance of a lymph node is seen in cases of lymphoma infiltration [ 37 ]. Infection can appear similar to malignant nodes because of necrosis and abscess formation, which appears as hypoechoic regions on gray-scale US.…”
Section: Lymph Nodesmentioning
confidence: 99%
See 3 more Smart Citations
“…A global hypoechoic (i.e. pseudocystic) appearance of a lymph node is seen in cases of lymphoma infiltration [ 37 ]. Infection can appear similar to malignant nodes because of necrosis and abscess formation, which appears as hypoechoic regions on gray-scale US.…”
Section: Lymph Nodesmentioning
confidence: 99%
“…In lymphoma, new capillary circulation increases the blood flow to the node, producing a hyperenhancing CEUS appearance. Increased flow through normal hilar vessels in reactive lymph nodes results in hyperemia that can be difficult to distinguish from lymphoma [ 14 , 37 ].…”
Section: Lymph Nodesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a new ultrasonic diagnostic technique for normal and enhanced lesions, which can effectively evaluate intratissue perfusion and microcirculation. Previous studies have shown that the CEUS yields superior results in the diagnosis of cervical benign lymph node diseases and tumor lymph node metastasis, with higher accuracy compared with the conventional ultrasound (12,13). However, data on the use of CEUS in differential diagnosis of cervical lymph node metastasis from PTC and tuberculous lymphadenitis remain scant.…”
Section: Introductionmentioning
confidence: 99%